Investor behavior under the Covid-19 pandemic: the case of Indonesia - Novi Swandari Budiarso; Abdul Wahab Hasyim; Rusman Soleman; Irfan Zam Zam; Winston Pontoh (Investment Management & Financial Innovations, 2020)
This study begins with the assumption that the existence of abnormal circumstances will force investors to take measures to protect their investments in the capital market. Recently, the stock index in the Indonesian market has been declining and continued to fall until the end of April 2020 due to the impact of the Covid-19 pandemic. In terms of efficient market theory, prospect theory and signaling theory, this study aims to analyze the relationship between risk and return in the Indonesian capital market during the Covid-19 pandemic as a manifestation of investor behavior. To test hypotheses, the correlation test, the independent sample t-test and the Cohen test for 629 public firms with 52,836 observable data are used. The findings show that for financial sectors and non-financial sectors, the fourth period differs from previous periods when the relationship between systematic risk and stock returns is positive, although only non-financial sectors have a significant effect. The results show that efficient market theory, prospect theory and signaling theory are consistent with the phenomena around the Covid-19 pandemic in Indonesia. In addition, Cohen’s test results suggest that government policies in the face of the pandemic are successful in stimulating the market.